eling the Humanitarian Intervention Dilemmas and Failures of the United Nations in “Quo Vadis, Aida?” Film - Purwanto, Cynthia Syukur (Kelompok Studi Mahasiswa Pengkaji Masalah Internasional Unpar, 2024)
This journal explores the United Nations' (PBB) intervention in the conflict between Bosnia-Herzegovina and Serbia, with a particular focus on the tragic events depicted in the film